EL PAPEL ESTRATÉGICO DE LA ENFERMERÍA EN HERIDAS CRÓNICAS, MÁS ALLÁ DEL CUIDADO CONVENCIONAL - Xiques-Molina, Wolmark; Pérez-Camacho, Katrwin; Visconti-Lopez, Fabriccio J. (Ciencia y Enfermería, 2026)